Perspectivas e potencialidades da agroindústria brasileira do frango com a indústria 4.0 - Bastiani, Débora Soares de (2020)
Since the launch of Germany's technological development plan, called High-Tech Strategy 2020, in 2010, the concept of Industry 4.0 has come to be known worldwide as an innovative idea to strengthen the manufacturing industry.In the business of producing meat and chicken meat products, the implementation of principles and pillars of this new concept has been sought, mainly given the high level of competitiveness in the national and international Market. In Brazil, in the poultry agribusiness sector, the implementation of these technologies is still in a slow process due to the high cost, the organizational culture and, mainly, the uncertain return on investment. The study focuses on the characterizationof Industry 4.0 for the reality of the poultry agribusiness, whose objective is to identify the current situation of Brazilian agribusinesses linked to the slaughter of poultry, how they are preparing and dealing with the prospects and potential of Industry 4.0. Three important dimensions, technology, people and management, are taken into account, enabling their characterization and guidance in order to assist future deployments in this segment. Based on a systematic literature review, it was possible to establish the elements that characterize Industry 4.0 for poultry agroindustries, allowing the elaboration of an instrument that helped in the survey and obtaining information. Then, an exploratory field research (case studies) was carried out in two companies of sizes and technology levels employed in their divergent machines and processes, which made it possible to identify with the users the facilities and difficulties in relation to the three dimensions studied (people, technology and management), in addition to raising potential needs for companies in the industry studied to integrate with the perspectives of Industry 4.0. The elaborated instrument allowed the gathering and obtaining of information, identifying the current situation of brazilian agroindustries linked to the slaughter of poultry. Through the case studies carried out, it is observed that the company that has more automation in its plant is a little more prepared for this new productive paradigm of Industry 4.0 than the other company studied. The availability of equipment and technological innovation was identified for this line of activity, interest of professionals working in these industries and the use of tools that allow real-time vision as the main facilities for the implementation of Industry 4.0 in this sector. The main difficulties and potential needs identified the lack of capacity building by companies, lack of planning and investments in technologies necessary for the implementation of Industry 4.0, alignment of the strategy and organizational culture of companies for this new concept of industry, preparing people for this new professional profile, using technologies that process large volumes of data and tools that allow systems integration. With the results obtained in this research, it was possible to identify that the Brazilian poultry agribusiness, despite investments in modern machinery and equipment, has a long wayto integrateinto the new productive paradigm. Even the largest capacity industries, considered more automated, still have a lot to improve in all three dimensions studied.